THE EXISTENCE OF ESCHERICHIA COLI ON GRILLED INTESTINES (SATE USUS) AND ITS RELATED FACTORS IN A TRADITIONAL FOOD STALL AT MALIOBORO TOURISM AREA, YOGYAKARTA, INDONESIA - Suryani, Dyah; Astuti, Fardhiasih Dwi; Indriyani, Mila Melinda; Suyitno, Suyitno; Maretalinia, Maretalinia; Yulianto, Aris (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Grilled intestines (sate usus) is one of favorite foods in Yogyakarta, not only because of its delicious taste, but also because of its cheap price and unique shape. To ensure the food safety, the existence of Escherichia coli was examined. Objective: To identify factors related to the existence of Escherichia coli on sate usus in one of traditional food stall (angkringan) at Malioboro tourism area.Methods: This is a cross-sectional study involved 38 respondents selected using accidental sampling from April to May 2019. The determinants of the existence of Escherichia coli include the sellers' knowledge, behavior, personal hygiene, food serving practice, and sanitation facilities. The existence of Escherichia coli was tested using a laboratory test. The correlations between Escherichia coli and its determinants were analyzed using Chi-Square tests and simple logistic regression.Results: The result of the laboratory test showed that 39.5% of sate usus positively contained Escherichia coli bacteria. Among all factors, only food serving practice was associated with the existence of Escherichia coli. The sellers who had poor food serving practice were three times more likely having Escherichia coli on their sate usus (OR= 3.30, 95% CI= 1.967-5.536).Conclusion: These findings suggested that public health providers should design programs to provide training for food sellers in order to serve food well and healthily. This is crucial to do to ensure the food safety in the tourist areas in Indonesia.